2023
DOI: 10.3390/ijms24119681
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3-I148M Variant Promotes the Progression of Liver Fibrosis by Inducing Mitochondrial Dysfunction

Abstract: Patatin-like phospholipase domain-containing 3 (PNPLA3) rs738409 polymorphism (I148M) is strongly associated with non-alcoholic steatohepatitis and advanced fibrosis; however, the underlying mechanisms remain largely unknown. In this study, we investigated the effect of PNPLA3-I148M on the activation of hepatic stellate cell line LX-2 and the progression of liver fibrosis. Immunofluorescence staining and enzyme-linked immunosorbent assay were used to detect lipid accumulation. The expression levels of fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…At the conclusion of the experimental time course, 96-well LAMPS were labeled with BODIPY 581/591 C11, a ratiometric fluorescent sensor for LPO, to determine the ratio of oxidized BODIPY (green) to reduced BODIPY (yellow) reflecting the overall LPO status within the model. Consistent with recent studies (76, 77), a significant increase in the ratio of Oxidized BODIPY/reduced BODIPY was observed in PNPLA3 GG variant 96-well plate LAMPS compared to the CC wild type in each media condition, demonstrating increased ROS production associated with the PNPLA3 GG variant (Fig S4A and S4B) .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…At the conclusion of the experimental time course, 96-well LAMPS were labeled with BODIPY 581/591 C11, a ratiometric fluorescent sensor for LPO, to determine the ratio of oxidized BODIPY (green) to reduced BODIPY (yellow) reflecting the overall LPO status within the model. Consistent with recent studies (76, 77), a significant increase in the ratio of Oxidized BODIPY/reduced BODIPY was observed in PNPLA3 GG variant 96-well plate LAMPS compared to the CC wild type in each media condition, demonstrating increased ROS production associated with the PNPLA3 GG variant (Fig S4A and S4B) .…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have shown that the increased steatosis sociated with MASLD progression impairs mitochondrial oxidative capacity resulting in the increased production of reactive oxygen species (ROS) (74, 75). Moreover, it has also recently been demonstrated that the PNPLA3 GG variant promotes the progression of MASLD by inducing mitochondrial dysfunction (76, 77). We next quantitatively assessed lipid peroxidation (LPO) in a 96-well plate format LAMPS (62) constructed with PNPLA3 GG variant or CC wild type hepatocytes and nonparenchymal cells (LSECs, LX-2 cells and THP-1 cells) that were maintained in NF, EMS, or LMS media for 5 days (Fig S4) .…”
Section: Resultsmentioning
confidence: 99%
“…The pharmacologic inhibition of acetyl-coenzyme A carboxylase, which is involved in de novo lipogenesis, prevented HSC activation in a rodent model of nonalcoholic fatty liver disease [30]. This suggests that lipid challenge, fatty acid oxidation, de novo lipogenesis induction, and the presence of PNPLA3 polymorphisms involved in the steatotic liver might influence HSC activation and, thus, fibrosis progression [30][31][32].…”
Section: Discussionmentioning
confidence: 96%
“…Genetic association studies have highlighted that some of the genetic factors which influence the individual's susceptibility to SLD are strongly associated with lipid droplet biogenesis and turnover (Table 1) [29,34,36,[39][40][41][42][43]. Specifically, certain genetic variants encoding lipid droplet proteins have been identified as instrumental in the onset and progression of SLD.…”
Section: Genetic Factors Associated With Lipid Droplets and Steatotic...mentioning
confidence: 99%